Isolated Sub-50 Attosecond Pulse Generation in the Combined Mid-Infrared Laser Field (Journal of Atomic and Molecular Sciences, 2013)
We theoretically study high-order harmonic and isolated attosecond pulse generation from a model helion ion in the combination of the mid-infrared (mid-IR) laser and an extreme ultraviolet (xuv) pulse. It is shown that, for the low laser intensity, the harmonic cutoff is at about 657th order, and the supercontinuum with a 287-eV bandwidth is formed. For the high laser intensity, the spectral cutoff is enlarged to 1795th order, and the supercontinuum is broadened to 834 eV. In the two cases, both the long quantum path selection and the enhancement of the supercontinuum are achieved. Especially for the relatively high laser intensity, pure isolated sub-50 as pulses can be directly obtained by superposing an arbitrary 87-eV harmonics in the supercontinuum from 450th to 1590th order.
Keywords: high-order harmonic generation; supercontinuum; isolated attosecond pulse; combined field.